2017
DOI: 10.1111/pbi.12783
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of plant‐produced African horse sickness virus‐like particles: implications for a novel vaccine

Abstract: SummaryAfrican horse sickness (AHS) is a debilitating and often fatal viral disease affecting horses in much of Africa, caused by the dsRNA orbivirus African horse sickness virus (AHSV). Vaccination remains the single most effective weapon in combatting AHS, as there is no treatment for the disease apart from good animal husbandry. However, the only commercially available vaccine is a live‐attenuated version of the virus (LAV). The threat of outbreaks of the disease outside its endemic region and the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…VLPs are composed of viral structural proteins but lack viral genome. They could be recognized easily by the immune system and show dramatic effectiveness because of the present of viral antigens in a conformation like virus [ 10 ]. It was reported that CPV VLPs with good immunogenicity could be produced by the eukaryocyte system [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…VLPs are composed of viral structural proteins but lack viral genome. They could be recognized easily by the immune system and show dramatic effectiveness because of the present of viral antigens in a conformation like virus [ 10 ]. It was reported that CPV VLPs with good immunogenicity could be produced by the eukaryocyte system [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we have shown in a recent study that vaccination against only one AHSV non-structural protein confers multi-serotype protection (Marín-López et al . manuscript in preparation), while the protection reached by VLP vaccination is serotype-specific 26 . The amplitude of the response in such study is similar to the serotype-specific response generated by vaccination against the surface protein VP2, responsible of the viral contact with the cellular receptor.…”
Section: Discussionmentioning
confidence: 98%
“…coat protein, is often coexpressed with a target protein to suppress gene silencing suppressors and greatly improves expression levels of heterologous genes (Qu et al, 2003;Thomas et al, 2003;Islam et al, 2019a); in addition, p38 itself accumulates to high levels in the plant cytosol. Many viral proteins are expressed at high levels and show a high degree of stability in plants (Dennis et al, 2018;Margolin et al, 2018). When we tested whether p38 induced accumulation of fusion proteins in the ER, we found that p38 fusion to the hLIF increased recombinant protein levels by 1.3-folds in plants; in fact, p38 increased protein expression to a greater extent than the M domain, which was shown to increase accumulation of ERtargeted proteins significantly (6-to 8-fold increase in level) in plants (Kang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%